An indispensable liberty : the fight for free speech in nineteenth-century America - Bulla, David W., 1959- (Southern Illinois University Press, 2016)
"This collection of eleven essays examines nineteenth-century legal and extralegal attempts to restrict freedom of speech and the press as well as the efforts of others to push back against those restrictions"--